OPEN GOVERNMENT: A BIBLIOGRAPHIC STUDY OF THE SEMARANG AND GWANGJU EXPERIENCES - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi (LPPM Universitas Abdurrab, 2023)
This study aims to analyze the open government bibliometrics of Semarang and Gwangju, two of the 110 local governments that are members of the Open Government Partnership (OGP). Semarang and Gwangju have jointly joined the OGP in 2020. This research uses a qualitative approach with a bibliometric analysis method. Research data was obtained from Google Scholar using Publish or Perish and then analyzed using Vosviewer. The results of this study indicate that from each of the 150 Semarang and Gwangju papers, there are 5470 citations, 42 h-index, 63 g-index, 116 keywords, 13 clusters, 1293 total link strengths, and 507 occurrences in the Semarang paper. Whereas in the Gwangju paper, there are 3650 citations, 30 h-index, 52 g-index, 143 keywords, 18 clusters, 1143 total link strength, and 479 occurrences. In the 2020–2022 timeframe, the Semarang government has established four open government policies, while Gwangju has two. There is harmony between the open government policies of these two local governments with studies produced by scholars, which allows a positive contribution to the Semarang and Gwangju open government policies.